The survival and cost-effectiveness analysis of adjunctive Chinese medicine therapy for patients with non-small cell lung cancer: a nationwide cohort study in Taiwan - Tang, Meng-Bin; Kuo, Wei-Yin; Kung, Pei-Tseng; Tsai, Wen-Chen (Frontiers in Pharmacology, 2024)
Introduction: Cancer, particularly lung cancer, is a significant global healthcare challenge. Non-Small Cell Lung Cancer (NSCLC) constitutes 85% of cases. Patients often seek alternative therapies like Chinese medicine alongside Western treatments. This study investigates the survival outcomes and cost-effectiveness of adjunctive Chinese medicine therapy for NSCLC patients in Taiwan. Methods: We utilized the National Health Insurance Research Database in a retrospective cohort study from 2000 to 2018, focusing on NSCLC patients diagnosed between 2007 and 2013. After propensity score matching 1:5 ratio, then compared patients with and without adjunctive Chinese medicine therapy. Survival outcomes, cost-effectiveness, and sensitivity analyses were conducted. Results: The study involved 43,122 NSCLC patients with 5.76% receiving adjunctive Chinese medicine. There is no significant associated between the risk of death and adjuvant Chinese medicine therapy until 181–365 days of adjuvant treatment could reduce the risk of death (HR = 0.88, 95% CI: 0.80–0.98). Cost-effectiveness analysis showed an incremental cost-effectiveness ratio of 880,908 NT/year. Conclusion: Adjunctive Chinese medicine therapy, particularly when administered for 181–365 days, significantly reduced the mortality risk among stage IV NSCLC patients. The cost-effectiveness aligns with willingness-to-pay thresholds, indicating economic benefit.